Interação entre sexo e obesidade na qualidade de vida de adultos assistidos pelo programa Médico de Família de Niterói - Torres, Karla Dala Paula (2013)
Introduction: Obesity has become a worldwide epidemic and is a risk factor for several chronic diseases. It is a multicausal phenomenon of difficult approach that impacts the quality of life. It is known that obese women in general have lower scores on elf-assessment of quality of life than obese men. However, we found no studies that have examined the biological interaction between gender and obesity for low-related quality of life (HRQoL). Objective: To verify the existence of biological interaction between sex and obesity on HRQoL measured by the SF-36, regardless of the presence of comorbidities. Methodology: This was a cross-sectional study based on data from CAMELIA study whose visits occurred between July 2005 and December 2006, with population assisted by the Family Doctor Program of Niterói (PMF). For the present study included individuals from 19 to 64 years, without severe comorbidities (n = 605). Obesity was defined by body mass index (BMI  30kg / m²). Quality of life was assessed by the SF-36. The low HRQoL was defined in total: the overall score of the SF-36 physical: physical component of the SF-36 and mental: mental component of the SF-36 dichotomized into score below the 1st quartile - low quality of life and greater than or equal - control. Variables were created for four exposure categories: obese women (+ +), non-obese women (+ -), obese men (- +) and non-obese men (-) as the reference category. Departures from additivity were observed and their confidence intervals of 95% were estimated from the delta method. Results: Obese women, even after adjustment, showed higher percentages of low overall quality of life, physical and mental health compared to non-obese men, with the largest associations in the physical (ORa = 2.13, CI = 1.08 to 4, 21) that the mental dimensions (ORa = 1.38, CI = 0.62 to 3.04). The excess risk due to interaction was statistically significant in physical dimensions. Conclusion: The results corroborate the hypothesis of biological interaction between sex and obesity on quality of life. This study contributes to public health with the warning that an excess of cases of low HRQOL is related to obesity and woman combination.